The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m115.691857
|View full text |Cite
|
Sign up to set email alerts
|

miR-346 Up-regulates Argonaute 2 (AGO2) Protein Expression to Augment the Activity of Other MicroRNAs (miRNAs) and Contributes to Cervical Cancer Cell Malignancy

Abstract: MicroRNAs (miRNAs) are a class of post-transcriptional regulators of gene expression, and AGO2 is essential for miRNA activity. In this study, we focused on the regulation of AGO2 by miR-346 and the consequences in cervical cancer cells. miR-346 enhanced the expression of AGO2, resulting in the increased activity of other miRNAs and contributing to the malignancy of HeLa cells. GRSF1 participated in the regulation of AGO2 by miR-346, and the middle sequence of miR-346 was vital for the synergy effect of miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 39 publications
1
43
1
Order By: Relevance
“…Increasing data findings have indicated miRNAs to be critical regulators of cancer-related processes, but it is still unknown the molecu lar mechanisms by which miRNAs modulate the behavior of cancer cells (26,27). miR-346 has been reported as an oncomir because it facilitates cell growth and metastasis in various human cancers (16)(17)(18)(19)(20)(21). This is the first study that indicates that ectopically expressed miR-346 can promote migration, proliferation, and invasion of liver cancer cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Increasing data findings have indicated miRNAs to be critical regulators of cancer-related processes, but it is still unknown the molecu lar mechanisms by which miRNAs modulate the behavior of cancer cells (26,27). miR-346 has been reported as an oncomir because it facilitates cell growth and metastasis in various human cancers (16)(17)(18)(19)(20)(21). This is the first study that indicates that ectopically expressed miR-346 can promote migration, proliferation, and invasion of liver cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…Emerging evidence suggests that the abnormal expression of miRNAs is involved in the invasion and metastasis, during the progression of various human cancers (14,15). miR-346 has been reported as an oncomir in various human cancers, including cutaneous squamous cell carcinoma (16), cervical cancer (17), prostate cancer (18), nasopharyngeal carcinoma (19), lung cancer (20) and breast cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that miR-346 might be an oncogenic miRNA in some cancers, including cervical cancer [21,22], cutaneous squamous cell carcinoma [23]. However, the functional role and mechanistic action of miR-346 in NSCLC remained largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Including Graves' disease [19], rheumatoid arthritis [20], cervical cancer [21,22], cutaneous squamous cell carcinoma [23]. Wang et al also found that miR-346 regulates osteogenic differen-tiation of human bone marrow-derived mesenchymal stem cells by targeting the Wnt/β-catenin pathway [24].…”
Section: Introductionmentioning
confidence: 99%
“…miR-183 targets MMP3 to inhibit invasion of CC cells [185] while miR-375 inhibits invasion by targeting transcription factor SP1 [186]. miR-205 [187] promotes invasion of EC cells and miR-346 promotes migration and invasion of CC cells by positively regulating AGO2 (argonaute 2) [188]. …”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%